The Factors Influencing The Success Of Executives In Local Chinese-Based Companies - Chong, Kim Fook (1997)
There are many contributing factors to the career success of management executives. This study investigates the effects of handwork, politics and family ties on career success of executives working in local Chinese-based companies. The uniqueness of these Chinese companies is their family-style business nature. The scope of the study is limited to the management executives of these companies. Data were collected by means of questionnaire survey, with the assistance of people who have frequent dealings with these companies. A total of 110 respondents were sampled from companies in Penang.